Longitudinal changes in fetal biometry and cerebroplacental hemodynamics in fetuses with congenital heart disease. (6th March 2017) - Ruiz, A.; Cruz‐Lemini, M.; Masoller, N.; Sanz‐Cortés, M.; Ferrer, Q.; Ribera, I.; Martínez, J. M.; Crispi, F.; Arévalo, S.; Gómez, O.; Pérez‐Hoyos, S.; Carreras, E.; et al.
ABSTRACT: Objectives: To determine the longitudinal behavior of fetal biometric measures and cerebroplacental hemodynamics throughout gestation in fetuses with congenital heart disease (CHD). Methods: Fetal biometry and Doppler hemodynamics (uterine artery (UtA), umbilical artery (UA) and fetal middle cerebral artery (MCA)) were measured serially in a cohort of consecutive fetuses diagnosed with CHD. Evaluations were made at various time points, from diagnosis (20–25 weeks) to delivery, with at least two measurements per fetus that were at least 2 weeks apart. Fetuses were classified into three groups according to the pattern of blood supply to the brain (placental vs systemic) that would be expected on the basis of the type of CHD. All parameters were transformed into Z ‐scores. A linear mixed model to analyze repeated measurements was constructed for each parameter to assess its behavior throughout gestation. Results: Four hundred and forty‐four ultrasound examinations were performed in 119 CHD fetuses, with a median of two measurements per fetus. The fetuses presented a small head at diagnosis (biparietal diameter (BPD) Z ‐score, −1.32 ± 0.99; head circumference (HC) Z ‐score, −0.79 ± 1.02), which remained small throughout gestation. UtA and UA pulsatility indices (PI) showed a significant increase towards the end of pregnancy, whereas no significant changes were observed in MCA‐PI or cerebroplacental ratio (CPR) with gestational age. Both MCA and CPR presented significant differences in longitudinal behavior between CHD groups, while BPD and HC did not. Conclusions: CHD fetuses have a relatively small head from the second trimester of pregnancy, regardless of the type of CHD anomaly, and increasing resistance in the UtA and UA as pregnancy progresses, suggestive of increasing degree of placental impairment. Our findings indicate the early onset of mechanisms that could lead to poorer neurodevelopment later in life. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.